Qualidade microbiana e aspecto visual de mandioca minimamente processada - DOI: 10.4025/actascibiolsci.v29i2.592 - Lund, Daniela Guerra (2007)
Microbial quality and visual aspect of minimally processed cassava. The hygienic-sanitary quality of minimally processed vacuum packaged and refrigerated cassava (4-7ºC), with 4-8 days of storage was evaluated. Three representative samples from 3 different lots of cassava were obtained from retail stores in Pelotas, Rio Grande do Sul State, Brazil. The following microbial counts were carried out in each sample: mesophilic, psychrotrophic, lactic and sulfide-reducing bacteria, total e fecal coliforms and yeast and molds. The presence of Salmonella was also investigated. Results of counts ranged from 4.7 x 106 to 6.3 x 108 CFU g-1 for mesophilic bacteria, 1.8 x 107 to 6.0 x 108 CFU g-1 for psychrotrophic bacteria, 2.8 x 107 to 3.8 x 108 CFU g-1 for lactic bacteria, 1.5 x 103 to > 1.1 x 106 for total coliforms, < 30 to 4.6 x 104 for fecal coliforms, 2.4 x 102 to 2.5 x 104 CFU g-1 for yeasts and molds and < 10 CFU g-1 for sulfide-reducing bacteria. Salmonella was not detected. The high counts of bacteria in the product suggest poor processing or storage practices.